2020
DOI: 10.3348/kjr.2019.0413
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Abdominal CT Using a Deep Learning-Based Denoising Algorithm: A Comparison with CT Reconstructed with Filtered Back Projection or Iterative Reconstruction Algorithm

Abstract: Objective: To compare the image quality of low-dose (LD) computed tomography (CT) obtained using a deep learning-based denoising algorithm (DLA) with LD CT images reconstructed with a filtered back projection (FBP) and advanced modeled iterative reconstruction (ADMIRE). Materials and Methods: One hundred routine-dose (RD) abdominal CT studies reconstructed using FBP were used to train the DLA. Simulated CT images were made at dose levels of 13%, 25%, and 50% of the RD (DLA-1, -2, and -3) and reconstructed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 24 publications
2
53
0
1
Order By: Relevance
“…The SNR and CNR values of high strength DLR images were higher than those of ASIR-V with 80 or 100% blending factor. Similar results were also reported in studies with different vendor systems and algorithms [10,14,15]. Both studies suggested that DLR has the potential to improve image quality and potentially reduce patient radiation dose.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The SNR and CNR values of high strength DLR images were higher than those of ASIR-V with 80 or 100% blending factor. Similar results were also reported in studies with different vendor systems and algorithms [10,14,15]. Both studies suggested that DLR has the potential to improve image quality and potentially reduce patient radiation dose.…”
Section: Discussionsupporting
confidence: 82%
“…DLR scored better on artifacts than 30% ASIR-V images in a previous study [12]. Another study reported no DLR related image artifacts [14]. A prior study has reported more frequent distortion artifacts with DLR [22].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In another study, Kim et al [ 23 ] investigated the effect of different loss functions on convolutional neural network (CNN)–based image denoising performance using task-based image quality assessment for various signals and dose levels. Shin et al [ 24 ] compared the image quality of low-dose CT images obtained using a deep learning–based denoising algorithm with low-dose CT images reconstructed using filtered backprojection (FBP) and advanced modeled iterative reconstruction (ADMIRE). They reported that deep learning techniques achieved better noise properties compared with FBP and ADMIRE reconstructions of low-dose CT images.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several deep learning networks for image-to-image translation have been reported, and they have enabled remarkable radiation dose reduction by image denoising [ 10 11 12 13 ]. Specifically, generative adversarial networks (GANs) have achieved state-of-the-art performance in image generation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%